Exploring trust and loyalty within grandparent-headed families on the Cape Flats and the impact of the church, as social support - Roberths, Tamlynn Jane (Stellenbosch : Stellenbosch University, 2020)
Thesis (MTh)--Stellenbosch University, 2020.